Embraced by the light - Eadie, Betty J. (Betty Jean), 1942-; Taylor, Curtis, 1956- (Placerville, CA : Gold Leaf Press, 1992)
Relates the near-death experience of Betty Eadie, and recounts the events that followed.
Keywords: Near-death experiences